Papillomaviruses in Human Cancers - Zur Hausen, Harald (Proceedings of the Association of American Physicians, 1999)
Papillomaviruses have proved to be the most complex group of human pathogenic viruses. Eighty-five genotypes have been fully characterized; approximately 120 additional isolates represent only partially characterized putative novel genotypes. Specific types, most notably human papillomavirus (HPV) types 16, 18, and a few others, have been shown to cause the majority of cervical cancers and their high-grade precursor lesions. The viral oncogenes E6 and E7 are required for the initiation and maintenance of the malignant phenotype in HPV-positive cancers. Proteins coded by these genes are multifunctional and interfere with important cell cycle regulatory proteins. Expression of viral oncogenes is tightly controlled in nondifferentiated keratinocytes by at least two signaling cascades, one operative at the functional level, the other at the transcriptional level. The latter has been partially characterized. Papillomaviruses are also suspected of playing a role in a subset of oropharyngeal cancers, in squamous cell cancers of the skin, and possibly also in esophageal cancers. Clinical trials are being conducted to test the preventive and therapeutic efficacy of HPV vaccines, directed particularly against HPV 16 and 18. If proven to be effective, their global application should have a measurable effect on the worldwide incidence of cancer.
First published: 31 March 2003
Gesehen am 30.01.2019